MAPPING THE INTELLECTUAL LANDSCAPE OF DECISION MAKING IN EDUCATIONAL LEADERSHIP: A BIBLIOMETRIC ANALYSIS FROM 2015 TO 2025 - Mat Shoib, Noor Ashikin; Talip, Roslee; Sukor, Nursuhaidah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This bibliometric analysis explores the intellectual landscape and research trends in educational leadership decision-making, aiming to map the scholarly output and identify influential patterns from 2015 to 2025. The study addresses a significant research gap by systematically examining how decision-making processes have been conceptualized and applied in leadership and management contexts across educational settings. Using the Scopus database as the primary data source, a search was conducted with the keywords “decision-making,” “leadership,” and “management,” refined to focus on relevant subject areas, including social sciences, decision sciences, and the arts and humanities. This process yielded 953 scholarly documents. The dataset was cleansed and standardized using OpenRefine to ensure consistency in keyword terminology. Bibliometric analysis was conducted using the Scopus built-in analyzer and VOSviewer software to visualize co-authorship networks, keyword co-occurrence, and citation patterns. The results reveal a growing trend in publications after 2018, with significant contributions from countries such as China, India, Australia, and the United States. Thematic clusters strongly focus on strategic decision-making, instructional leadership, and participatory governance models. Highly cited authors and journals were identified, offering insights into influential contributors and platforms within the field. The study concludes that research on educational leadership decision-making is gaining momentum, particularly in the context of complex educational reforms and the increasing demand for evidence-based leadership. These findings offer valuable implications for policymakers, academic leaders, and researchers by highlighting emerging themes and collaboration opportunities that can shape future investigations and leadership practices.